To solve the quadratic equation (x - 7)^2 - 94 = 0, we need to move the constant term to the other side of the equation.
(x - 7)^2 = 94
Now take the square root of both sides:
√[(x - 7)^2] = ±√94
x - 7 = ±√94
Next, add 7 to both sides:
x = 7 ± √94
So the solutions to the quadratic equation (x - 7)^2 - 94 = 0 are x = 7 + √94 and x = 7 - √94.
Solve the following quadratic equation using square roots: (x−7)2−94=0%0D%0A(%0D%0A%0D%0A−%0D%0A7%0D%0A)%0D%0A2%0D%0A−%0D%0A9%0D%0A4%0D%0A=%0D%0A0%0D%0A.
1 answer